Effects of skeleton structure on necrosis targeting and clearance properties of radioiodinated dianthrones. (2nd July 2016) - Zhang, Dongjian; Jiang, Cuihua; Yang, Shengwei; Gao, Meng; Huang, Dejian; Wang, Xiaoning; Shao, Haibo; Feng, Yuanbo; Sun, Ziping; Ni, Yicheng; Zhang, Jian; Yin, Zhiqi
Abstract: Necrosis avid agents (NAAs) can be used for diagnose of necrosis-related diseases, evaluation of therapeutic responses and targeted therapeutics of tumor. In order to probe into the effects of molecular skeleton structure on necrosis targeting and clearance properties of radioiodinated dianthrones, four dianthrone compounds with the same substituents but different skeletal structures, namely Hypericin (Hyp), protohypericin (ProHyp), emodin dianthrone mesomer (ED-1) and emodin dianthrone raceme (ED-2) were synthesized and radioiodinated. Then radioiodinated dianthrones were evaluated in vitro for their necrosis avidity in A549 lung cancer cells untreated and treated with H2 O2 . Their biodistribution and pharmacokinetic properties were determined in rat models of induced necrosis. In vitro cell assay revealed that destruction of rigid skeleton structure dramatically reduced their necrosis targeting ability. Animal studies demonstrated that destruction of rigid skeleton structure dramatically reduced the necrotic tissue uptake and speed up the clearance from the most normal tissues for the studied compounds. Among these 131 I-dianthrones, 131 I-Hyp exhibited the highest uptake and persistent retention in necrotic tissues. Hepatic infarction could be clearly visualized by SPECT/CT using 131 I-Hyp as an imaging probe. The results suggest that the skeleton structure of Hyp is the lead structure for further structure optimization of this class of NAAs.